Detecting a New Type of Stokes V Profiles Observed by Hinode in a Sunspot - Hashem Hamedivafa (Iranian Journal of Astronomy and Astrophysics)
A part of a mature sunspot including of umbrae and penumbrae is observationally examined to find photospheric dynamics. We analyze spectro-polarimetric observations of photospheric Fe~I lines with the Solar Optical Telescope aboard Hinode to find signatures of Doppler velocities on the Stokes V profiles. Stokes V profiles characterized by humps on both blue and red lobes with the same magnetic polarity as the sunspot umbrae were detected in both umbrae and penumbrae. These types of profiles have not been previously reported. Pixels whose Stokes V profiles show humps on, at least, either blue or red lobe are ubiquitous: 42.1% show both humps; 36.8% (3.7%) show only blue (red) hump. Umbra shows profiles having both blue and red humps. Investigating the Stokes V profiles characterized by humps implies that all types of these profiles are the same entity with different hump amplitudes. This means that both blue and red humps alter the Stokes V profiles either as explicit humps or as tail extension of the lobes. The magnetic fields of these hidden structures have to be weak and almost vertical. This implies that two humps cannot belong to a single-2nd-component. Bidirectional flows propagating along vertical magnetic fields as the result of redirection of outflows along the vertical magnetic field, after a magnetic reconnection, gives a possible mechanism producing adjacent upflows and downflows. Blue and red humps can be the Doppler effect signatures of these upflows and downflows, respectively.